Analisis Faktor Kunci Keberhasilan Implementasi Last Planner System untuk Peningkatan Kinerja Waktu pada Proyek Bendungan - Kussumardianadewi, Bernadette Detty; Husin, Albert Eddy; Susianti, Anti (Department of Civil Engineering, Diponegoro University, 2023)
Infrastructure development is crucial to the development of a nation’s economy. Based on data from the 2021 World Competitiveness Yearbook, Indonesia's infrastructure is ranked 57th out of 64 countries and one of the assessment criteria is related to water resources. Water resource management in Indonesia is still faced with fundamental challenges, including the limited water storage capacity in Indonesia so alternative water resources development is needed, among which is through the construction of dams. In practice, dam projects are very vulnerable to time delays. One of the solutions to this problem is the application of the last planner system method. The implementation of the last planner system can help create major improvements in project planning, increase workflow and productivity, and reduce project time and site accidents. This research has an update regarding the implementation of the last planner system method on a dam project and analyzing the key success factors using SEM-PLS. According to the study's findings, the key success factors of the implementation of the last planner system method on dam projects are budget plan, work schedule, clarity of scope of work, work plan, planning process, and weekly plan